Strategi Adaptasi Terhadap Dampak Perubahan Iklim di Pesisir Kota Makassar - Angelia Khairunnisa; Slamet Trisutomo; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Climate change directly or indirectly affects various aspects of human life. The issue of world climate change which has resulted in sea level rise also threatens the Coastal Area of ​​Makassar City Based on the 2013 Makassar BNPB Climate Change Vulnerability Study, it was identified that the biggest climate threat for the coast of Makassar City was sea level rise. This danger will affect various parts of the coast in different ways, so understanding the various consequences, both primary and secondary impacts, is important to find ways to reduce vulnerability to them. This research was conducted by referring to the vulnerability approach consisting of several stages; examine vulnerabilities, understand the impacts of climate change, and propose adaptation strategies. First, checking vulnerability is done by assessing the impact of climate change that occurs in Makassar City using the CVI method (Coastal Vulnerability Index) based on three indicators, namely exposure, sensitivity and adaptive capacity. Second, understanding the impact of climate change based on the results of the matrix determining the class of vulnerability of the region. The results obtained are the level of vulnerability of the coastal area of ​​Makassar City to the effects of climate change showing three categories of vulnerability, namely, low, medium and high. So that the strategies that can be implemented are accommodative strategies and protective strategies. The accommodative strategy is implemented in area that have a low and moderate level of vulnerability while a protective strategy in high levels of vulnerability.